Tenuazonic acid production is dispensable for virulence, but its biosynthetic gene expression pattern is associated with the infection of Pyricularia oryzae. Issue 1 (10th November 2021) - Kashiwa, Takeshi; Motoyama, Takayuki; Yoshida, Kazuko; Yun, Choong-Soo; Osada, Hiroyuki
ABSTRACT: Tenuazonic acid (TeA) is a toxin produced by the rice blast fungus Pyricularia oryzae . Although knockout of the TeA biosynthetic gene TAS1 did not affect the virulence of P. oryzae, constitutive TAS1 expression suppressed its infection. TAS1 expression was induced alongside transition of P. oryzae infection behavior. The results suggested that controlling TeA biosynthesis is important for P. oryzae infection.